Mean streets homelessness, public space, and the limits of capital - Mitchell, Don 1961- (The University of Georgia Press, 2020)
"Mean Streets offers, in a single, sustained argument, a theory of the social and economic logic behind the historical development, evolution, and especially persistence of homelessness in the contemporary city. By updating and revisiting thirty years of research and thinking, Don Mitchell explores the conditions that produce and sustain homelessness, and how its persistence relates to the way capital works in the urban built environment. Consequently, he unpacks the structure, meaning, uses, and governance of urban public space. As one reviewer commented, "thinking about the histories under which the homeless have been produced and regulated is vital." Mitchell traces his argument through two sections: a broadly historical overview, followed by an exploration of recent Supreme Court jurisprudence that also expands the discussion beyond the regulation of the homeless and the poor, arguing that this has 'metastasized' to become more general issue, affecting all urbanites"--
Keywords: Obdachlosigkeit; Stadt; USA; Homelessness / United States; Public spaces / United States; Urban policy / United States; Homelessness; Public spaces; Urban policy; United States